CULTIVATING STUDENTS' TALENTS AND INTERESTS THROUGH MORNING ASSEMBLY ACTIVITIES AT STATE ELEMENTARY SCHOOL 088 PANYABUNGAN - Ainul Padilah; Juliana Syafitri; Nur Azizah Zulkifli; Nur Aidah; Nurmaidah Nurmaidah; Ainun Sakiah; Salsa Nabila Hasan Nasution (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study explores how morning assembly activities can be a medium for fostering student talents and interests at SD Negeri 088 Panyabungan. Morning assembly activities are held every Saturday, where different classes take turns showcasing their talents and interests in various art forms, such as singing, drama, and dancing. The research approach chosen was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results show that morning assembly activities provide a forum for student self-expression, fostering self-confidence, strengthening a sense of community, and helping teachers recognize student potential in greater depth. This activity also stimulates students to actively participate in the school's arts and culture world, so that their talents and interests can grow and develop sustainably. This study recommends that schools design a more structured morning assembly schedule and involve the support of parents and supervising teachers so that the development of student talents and interests takes place optimally.